Fuzzy analytic hierarchy process to solve the child abuse problem / Norpah Mahat and Nur Farhiyah Zulkofli - Mahat, Norpah; Zulkofli, Nur Farhiyah (UiTM Cawangan Perlis, 2020)
Children always bring so much joy, happiness and laughter to one's life. Unfortunately, they were always being the target to abuse. The effects of child abuse are severe and long-lasting to the victims. While recently Malaysia statistic has reported a significant increment of child abuse cases that have reported in this country. The graph presents a steady growth of these cases without showing any sign of ecrement. The victim is only a child, who is innocent, powerless, and incapable to protect themselves without any help, care and support from people around themselves. Hence, this study purposed to determine the main factors that contribute to child abuse cases in Malaysia. In this study, FAHP (Fuzzy Analytic Hierarchy Process) are used to determine the main factors that contribute to the child abuse cases in Malaysia. The data was collected from the official portal of the Department of Social Welfare, Ministry of Women, Family and Community Development. The factors used in this study are family dispute, followed boyfriend, unknown, financial problem, negligence of parents or guardian, illegitimate child, stepchild, adopted child or preserved by others during childhood, alcoholic, gambler, drug addicts, abuser suffered mental health problems, abuser was formerly abused and others. Three criteria consist of perpetrators, type of carer occupations and gender of the victim are taken into consideration. The result shows the family dispute was determined as the main factors of child abuse compared to the other factors. This finding is very important for the use of the Ministry of Women, Family and Community Development responsible for the formulation of policies and guidelines on the development of children, women and families in Malaysia. This effort is expected to reduce the rate of child abuse in turn giving them a better life.